Comparison of clinical outcomes between percutaneous coronary intervention for the de novo lesion versus in-stent restenosis lesion. (14th October 2021) - Takeuchi, M; Dohi, T; Fukase, T; Nishio, R; Takahashi, N; Endo, H; Doi, S; Kato, Y; Okai, I; Iwata, H; Okazaki, S; Isoda, K; et al.
Abstract: Background and objective: Percutaneous coronary intervention (PCI) with metallic coronary stent (bare-metal stents [BMS] and drug-eluting stents [DES]) implantation is most frequently performed therapeutic procedures for coronary artery disease. In-stent restenosis (ISR) is a critical drawback of metallic coronary stents. Incidence of ISR has been reported in up to 30% after BMS implantation. The use of DES has greatly reduced the proportion of restenosis compared with the BMS. However, ISR still remains the primary concern after PCI even in the contemporary DES era, and thought to be associated with worse clinical outcomes. However, comparative data on ISR and de novo lesions are rare. Purpose: The aim of the present study was to compare the clinical outcomes after PCI for the de novo lesion and the ISR lesion. Methods: We performed a retrospective analysis of patients who underwent PCI between 2013 and 2020. The incidences of major adverse cardiac and cerebrovascular events (MACCE) and all-cause death were evaluated. MACCE was defined as composite of cardiovascular death, non-fatal myocardial infarction, and stroke. Results: In this study, 1538 patients were enrolled and divided into two groups: PCI for de novo lesion group (n=1258, 81.8%), and PCI for ISR lesion group (n=280, 18.2%). Patients in the ISR lesion group were significantly older and had higher prevalence of hypertension, diabetes mellitus, dyslipidemia and chronic kidney disease than patients in the de novo lesion group. During a median follow-up period of 1.9 years, Kaplan-Meier curves showed no significant differences in the incidences of MACCE (log-rank, p=0.86) and all-cause death (p=0.84) between two groups. After adjustment for other covariates, PCI for ISR lesion were not significantly associated with MACCE (hazard ratio [HR], 1.10; 95% confidential interval [CI], 0.61–1.97; p=0.76) and all-cause death (HR, 0.93; 95% CI, 0.56–1.56; p=0.79) Conclusion: PCI for the ISR lesion was not associated with worse clinical outcomes compared with PCI for the de novo lesion. FUNDunding Acknowledgement: Type of funding sources: None.